Building mobile apps with HTML, CSS, and JavaScript : principles of mobile interface design (O'Reilly Media, 2015)
"Serving customers a substandard website experience on their mobile devices costs you sales, hurts your brand, and turns your customers away. In this video workshop, mobile strategy consultant Jonathan Stark shows your in-house web team how to use the HTML, CSS, and JavaScript skills they already have to build killer mobile websites and apps. Many companies opt to learn native mobile technologies instead, but familiar web tools let you design sites that work on multiple devices and help you build apps that can access native mobile device APIs. Your team already possesses 90% of the knowledge and skills they need to get started. This workshop will help them gain confidence that comes from direct experience."--Resource description page.